Adaptation and Validation of The Work-Family Conflict Scale (Wafcs) For Use In Bahasa Indonesia - Quraini, Az-Zahra Rizqi; Wirawan, Hillman; Nurkholis, Uswatun Hasanah; Fahreza, Rizky Nur; Putri, Findra Anugrah (Universitas Negeri Makassar, 2025)
This study aims to adapt and validate the Work-Family Conflict Scale (WAFCS) into an Indonesia version, in order to ensure its overall validity and reliability within the Indonesian cultural context. The adaptation process follows international guideline standards, in encompassing forward translation, back translation, expert evaluation, and field testing on 252 workers in South Sulawesi Province, Indonesia. Reliability analysis showed consistent and excellent results with an overall omega (ω) coefficient of .92, as well as .88 and .89 for the work-to-family and family-to-work dimensions, respectively. Construct validity testing through Confirmatory Factor Analysis (CFA) indicated that although most items had significant factor loadings and adequate variance, the model fit indices (CFI = .87; TLI = .83; RMSEA = .16) did not fully meet ideal statistical criteria. These findings suggest that the two-factor structure of the WAFCS can still be substantially replicated. However, interpretations of work and family role conflict are influenced by local social and cultural contexts of the population. Thus, although the WAFCS has not yet achieved an ideal statistical model fit, the instrument still can be regarded as a reliable and relevant tool to measure work-family conflict in Indonesia, while considering further adjustments to the model structure and a broader target population.